Self-reported competence in long term care provision for adult cancer survivors: A cross sectional survey of nursing and allied health care professionals. (January 2016) - Faithfull, S.; Samuel, Carol; Lemanska, Agnieszka; Warnock, Clare; Greenfield, Diana
Abstract: Background: Cancer survival is increasing as patients live longer with a cancer diagnosis. This success has implications for health service provision in that increasing numbers of adults who have received cancer therapy are requiring monitoring and long-term health care by a wide range of practitioners. Given these recent trends there is a need to explore staff perceptions and confidence in managing the consequences of cancer diagnosis and treatment in cancer survivors to enhance an integrated cancer service delivery. Objective: This study examines the self-reported perceptions of competence in nurses and professionals allied to medicine providing survivorship services caring for adults after cancer treatment in both secondary and primary care. Design: A cross sectional survey of the adult cancer workforce using a self-assessment tool for assessing confidence in providing long-term cancer patient management. This study was a health service evaluation. Setting: The study was conducted within the United Kingdom. Participants: Respondents were 618 health care professionals of these 368 were specialist adult cancer nurses in oncology and the community setting and 250 cancer allied health professionals. Method: The survey tool was developed with experts in cancer management, nurses professionals allied to medicine such as physiotherapists and dieticians, educationalists, patient groups as well as health service managers. Competence was assessed in 4 domains clinical practice, symptom management, care co-ordination and proactive management. Perceptions of training needs were also ascertained. Data were collected using an Internet survey distributed through cancer services, community settings and professional institutions. Results: In total 618 practitioners who responded were providing services for adults' 1-year post cancer therapy. Practitioners felt confident in managing psychosocial care and communicating with patients. Deficits in self-reported confidence were found in long-term medications management, care planning, long-term and complex symptom management, for those providing dimensions of care coordination and proactive care. Differences in confidence were seen between practitioner groups. Community nurses felt less skilled in managing adult cancer patients long-term. Conclusions: Nurses and allied health professionals self-reported confidence, in managing all areas of care for adult cancer survivors, is variable with deficits in important areas of practice. Despite this being a small proportion of practitioners who are working in cancer care, those responding had perceived gaps in knowledge and educational needs. In providing cancer aftercare there is a requisite shift to proactive care, supported self-management and collaborative management if patient's long-term consequences of cancer and its treatment are to be addressed. Implications for practice: If health care providers are to transform cancer survivor services then investment is required in education and capability planning across nurses, allied health professionals in both the hospital and the community setting.